Investigating links between Trichomonas vaginalis, T. vaginalis virus, Mycoplasma hominis, and metronidazole resistance - Rowen Govender; Nonkululeko Mabaso; Nathlee S Abbai (Journal of Infection in Developing Countries)
Introduction: Trichomonas vaginalis (TV) is the etiological agent of the common non-viral sexually transmitted infection (STI), trichomoniasis. TV can inherently harbour Mycoplasma hominis and Trichomonas vaginalis virus (TVV) species. Endosymbiosis of TV with M. hominis and TVV may contribute to metronidazole resistance in this pathogen. This study determined the prevalence of TVVs across clinical isolates of TV, as well as the symbiosis between TV, TVV, and M. hominis in relation to metronidazole resistance.